PENGARUH GOOD CORPORATE GOVERNANCE, PROFITABILITAS DAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP NILAI PERUSAHAAN - Windasari, Okta; Riharjo, Ikhsan Budi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThe purpose of research is to find empirical evidence of (a) the influence of good corporate governance mechanism, profitability and corporate social responsibility disclosure to the firm value, (b) the influence of good corporate governance mechanism and the profitability level of corporate social responsibility, (c) the influenceof good corporate governance mechanism to thefirm value and corporate social responsibility as the intervening variable, (d) the influence of the profitability level of firm value and corporate social responsibility as the intervening variable. This research uses secondary data and the samplesare manufacturing companies which are listed in Indonesia Stock Exchange (IDX) in 2011-2014 periods. The samples are 37 companies with 148 observations. The data analysis has been done by using multiple linear regressions analysis and Path Analysis test. The result of the research shows that good corporate governance and corporate social responsibility does not give any influence to the firm value. Profitability give positive influenceto the firm value. Good corporate governance give positive influence to the corporate social responsibility. Profitability does not give any influenceto the corporate social responsibility. Corporate social responsibility is not the intervening variable in the influence mechanism of good corporate governance and profitability to the firm value.Keywords: good corporate governance, profitability, corporate social responsibility, firm values.